The Juxtaposition of Risk and Resilience in Heritage Areas - Ida Cahyandari, Gerarda Orbita; Suratman; Mardiatno, Djati (Journal of Architectural/Planning Research and Studies (JARS), 2025)
Risk and resilience often enter the discussion with respect to hazard and disaster. In accordance with the meaning of juxtaposition, these two issues often are connected to each other but with contrasting effect. This paper aims to determine integrated factors used in assessment and strategies to reduce risk and to improve resilience in heritage areas. The method was based on observations and questionnaires that were undertaken in the protected heritage areas of Jeron Beteng inside the fort of Yogyakarta Palace, Indonesia. A literature review on risk and resilience factors preceded the formation of the questionnaires. The first questionnaire collected data from the owners or dwellers of the heritage sites, while the second questionnaire addressed the inhabitants of the surrounding area of the heritage sites. The field observation acquired information through visual assessment of heritage buildings, the surrounding communities, and their environments. The quantitative analysis applied a Likerd-like scale to score the questionnaires. The calculation represented the value of risk and resilience according to the score of attributes and each entity. The qualitative analysis explained essential risk and resilience factors by comparing the value. Historical precedents and demographic data support the analysis and understanding of the contextual phenomenon in the area. The juxtaposition of risk and resilience reveals the category of community and heritage entities (both tangible and intangible) at the macro- and micro- scales. Community is the main factor that connects risk and resilience in environmental, building, cultural, and hazard-disaster attributes. The intangible “heritage entity” and its surrounding community depend on each other, especially in relation to building and cultural attributes. The community surrounding the heritage building affects the improvement of resilience in macro-scale. The heritage building as a single entity influences risk reduction at the micro-scale. There are important roles of responsive community and maintained heritage buildings for enhancing the resilience of heritage area.